La guerra contra los filibusteros y la nacionalidad costarricense - Quesada, Juan Rafael (2016)
The National War of 1856-57 is the most significative historical experience for Costa Rica. Therefore, this article studies how the war against U.S. filibusterism helped to create nationhood since it was a collective effort that substituted the war of independence. The National War is also a source of poetic inspiration and the Clarín Patriótico o Colección de canciones otras poesías compuestas en Costa Rica en la guerra contra los filibusteros invasores de Centroamérica edited by Tadeo Nadeo Gómez is a proof of it. Those songs were first published in the press and then in this booklet dated 1857. Through the study of the Clarín Patriótico and other popular manifestations we conclude that the Costa Rican population responded positively to the "clarinada" made by President Juan Rafael Mora and Archbishop Llorente y Lafuente in 1855. Because of political reasons the name of Juan Rafael Mora was shadowed, but it is obvious that independence, sovereignty and nationhood were defended in many trenches and especially through the trenches of ideas. The Clarín Patriótico was a key element to recover those patriotic songs and poems that motivated and promoted citizenship in antebellum Costa Rica.